Pengaruh Kualitas Produk, Kepercayaan, Dan Kemudahan, Terhadap Keputusan Pembelian Pada E- Commerce Shopee - mulyani, Sri (LPPM Universitas Dharma Andalas, 2025)
This research aims to determine the influence of product quality, trust and convenience on purchasing decisions at Shopee e-commerce (case study of undergraduate students at the Faculty of Economics, Department of Management). The population in this study were students from the Faculty of Economics, Department of Management. The collection technique used the Slovin formula which was obtained by 84 respondents. The data used are validity and reliability tests, data analysis techniques using classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results of the t test research show that (1) product quality has a significant effect on purchasing decisions with a regression coefficient value of 2,108 and a probability value of 0.038 which means < 0.05, (2) Trust has a significant effect on purchasing decisions with a regression coefficient value of 56,093 and a value probability 0.000 which means < 0.05 and (3) Convenience has a significant effect on purchasing decisions with a regression coefficient value of 33,755 and a probability value of 0.000 which means <0.05. The results of the f test show that product quality, trust and convenience simultaneously (together) influence purchasing decisions with the regression coefficient obtaining a significant value of 0.000 < 0.05.